Student experiences of research methods education in college-based higher education. Issue 3 (3rd July 2018) - Turner, Rebecca; Sutton, Carole; Gray, Claire; Stevens, Sebastian; Swain, Julie
ABSTRACT: Research methods education is a challenging area for lecturers and students to engage with; students regularly demonstrate negative dispositions to research methods and lecturers struggle with issues such as curriculum marginalisation. However, employers increasingly demand graduates equipped with skills as researchers. Consequently, in university-based higher education, there has been investment to support research and good practice in this area. In contrast, limited attention has been paid to research methods education in college-based higher education. We report the outcomes of a small-scale national study designed to capture contemporary insights in research methods provision in college-based higher education. Drawing on data from two national surveys, we report student attitudes to, and experiences of, research methods and strategies employed by lecturers to teach and assess research methods. Students demonstrate positive attitudes to research methods, receptive to their research methods education and can see their applicability to 'real life' situations. However, the data demonstrate that the breadth of their research methods education is limited, potentially having implications for the development of skills such as critical evaluation of research outcomes, and students longer-term development as researchers. We conclude by highlighting future research directions and curriculum development to promote research methods education in college-based higher education.